The Influence of Work Culture, Organizational Commitment, and Incentives on Employee Performance in the Trade and Cooperative Service Micro Business in Ponorogo Regency - Wahyuni, Sri; Bambang Supriadi; Mokhamad Natsir (Journal of Scientific Insights, 2025)
This study aims to examine the influence of work culture, organizational commitment, and incentives on employee performance at the Ponorogo Regency Trade and Industry Office. Based on the development of the trade, cooperative, and micro-enterprise sectors in Ponorogo Regency which have shown a positive trend in recent years, with regional economic growth reaching 5.14% in 2023. The Ponorogo Regency Government, through the Trade, Cooperative, and Micro-Enterprise Office (Disperdagkum), has initiated various training and mentoring programs for Micro, Small, and Medium Enterprises (MSMEs) to increase competitiveness and market access. The research method used is a quantitative approach with an explanatory research type. Data were collected through a survey of Disperdagkum employees and analyzed using inferential statistical methods. The results of the study indicate that work culture and organizational commitment have a significant positive influence on employee performance. In addition, the incentives provided, both in financial and non-financial forms, contribute to increasing employee work motivation and productivity. Thus, to improve the effectiveness of Disperdagkum services, policies are needed that strengthen a positive work culture, increase employee commitment to the organization, and optimize the incentive system.